Comparative effect of different corticosteroids in severe community-acquired pneumonia: a network meta-analysis - Liangdong Zhu; Jia Zeng; Hui Li; Keyu Li; Xia Chen (BMC Pulmonary Medicine)
Abstract Background and objectives Severe community-acquired pneumonia (CAP) is a potentially fatal pulmonary disease. Although studies have investigated the efficacy and safety of corticosteroids for severe CAP, the results remain inconsistent. Moreover, there is a lack of sufficient evidence to rank the effects of different types of corticosteroids. The aim of this study is to elucidate the effects of different corticosteroids in patients with severe CAP. Methods We searched PubMed, Embase, Cochrane Library, and Web of Science comprehensively, encompassing all publications with a search deadline of March 31, 2024. Only randomized controlled trials (RCTs) involving the treatment of severe CAP with corticosteroids were included. The primary efficacy outcome was all-cause mortality, secondary efficacy outcome was mechanical ventilation (MV), and safety outcome was the incidence of serious adverse events (SAEs). Results A total of 11 studies, involving 2042 participants, compared four corticosteroids (hydrocortisone, dexamethasone, prednisolone, methylprednisolone). The included trials were all corticosteroid versus placebo comparisons, resulting in a star-shaped network. Among the four corticosteroids, only hydrocortisone was significantly more effective at reducing mortality than placebo (RR, 0.35; 95% CrI, 0.14–0.64). Additionally, hydrocortisone reduced the need for MV (RR, 0.73; 95% CrI, 0.51–0.93). Furthermore, subgroup analysis indicated that low-to-moderate doses, short-course corticosteroids are associated with a reduction in both mortality and the need for MV. Conclusion In the evaluated corticosteroid regimen, hydrocortisone might be an effective measure to reduce all-cause mortality in patients with severe CAP. Clinical trial number The present study is a meta-analysis and literature review, therefore clinical trial number is not applicable.